TEOLOGI KRISTEN DAN KEPEMIMPINAN KRISTUS DALAM GEREJA: FONDASI ILAHI BAGI PEMIMPIN ROHANI - Delvi Layuk Rongrean; Reny Toding Layuk, Mitra Marwan, Yulianti Kombong Sangapa', Asnawati Marson (ADISAM PUBLISHER, 2025)
Leadership in the church should be based on the example of Jesus Christ as the Great Shepherd who leads with love, protection, and sacrifice. The principles of Christ's leadership emphasize service, humility, and sacrifice, where a leader is not oriented towards power, but towards the welfare of the congregation. In addition, the role of the Holy Spirit is very important in guiding and equipping church leaders to remain faithful in carrying out their duties. The church today faces various challenges, both from within, such as authoritarian leadership and lack of integrity, and from outside, such as secularism and materialism. Therefore, the implementation of Christ's leadership must be realized with a relevant strategy without sacrificing the values of the Gospel. By following the principles of Christ's leadership, the church can remain strong in facing the challenges of the times and be a light to the world